Relationship between Psychosocial Factors in Wheelchair use with Quality of Life of Bed-Bound Elderly, Pathum Thani Province - ใจจำนงค์, สุกฤษฏิ์; มาอุ่น, กุลภัสร์ชา; กองเกิด, อภิญชาพัชญ์ (Journal of Health Science of Thailand, 2025)
This study aimed to examine the relationship between psychosocial factors (Satisfaction with wheelchair use, Self-efficacy in wheelchair use, and Wheelchair users' self-esteem) with the Quality of life of bed-bound elderly, Pathum Thani Province. Sample of 80 Bed-Bound Elderly by purposive sampling and selected using a multi-stage sampling technique. Researchers designed the questionnaire used to collect data. Data analyzed was descriptive statistics (Percentage, Means, and Standard Deviations) and Pearson’s Correlation Coefficient. The results showed that most sample groups have satisfaction with wheelchair use at a low level (x̅ = 30.9+6.781), Self-efficacy in wheelchair use at a high level (x̅ = 17.6+4.531), Wheelchair users' self-esteem at a moderate level (x̅ = 34.1+6.282), and Quality of life of bed-bound elderly at a moderate level (x̅ = 36.4+6.042). The relationship between psychosocial factors and the Quality of life of bed-bound elderly showed Wheelchair users' self-esteem was related to the Quality of life of bed-bound elderly (r = .292) significantly at .01 (p = .009). While the satisfaction with wheelchair use and Self-efficacy in wheelchair use was related to the Quality of life of bed-bound elderly (r = .137 and .081).